Strengthening of Continuous Reinforced Concrete Beams by Cfrp Laminates - Sabih Z. Al-Sarraf; Hisham Al-Hassani; Ali S. Al-Jebouri (Engineering and Technology Journal, 2013)
Experimental investigations of the behavior of reinforced concrete three-span continuous beams with 1200 mm length for each span, with cross-section 120 mm width and 180 mm depth strengthened by CFRP in flexure case of beams have been presented. The experimental program consisted of nine RC beams, which were strengthened at some locations with CFRP laminates and carefully designed to fail in flexure. The results show that the use of external CFRP laminate connected to the beams could enhance the ultimate flexural load capacity up to 102.88%.